DEMONSTRATIONS, BOYCOTTS, AND THREATS: COUNTER-HEGEMONY AGAINST THE ISRAEL INVASION IN THE GAZA STREET - Auliyaur Rachman; Munawar Ahmad (Arabic Literature Department, 2024)
This research explains the history of the founding the state of Israel, and its long conflict with Palestine. And how did the Hamas attack on October 7, receive a response from Israel which resulted in a humanitarian tragedy for the Palestinian peoples in the Gaza Strip. Israel's counterattack received criticism from the people around the world, they used various methods such as mass demonstrations in various countries, boycott action, various forms of threats, and pressure on their government to stop the war. The author tries to describe Israel's hegemony over Palestine in the Gaza conflict, which received resistance in the form of counter-hegemonic actions from the world community, the author calls this resistance the people emotional hegemony. The resistance movement really had an influence and impact on Israel and the countries that supported Israel's invasion, in the form of economic pressure, political issues and security. This study used descriptive qualitative method and Gramsci's theory of hegemony, based on this theory, Israel's invasion in the Gaza Strip, and killing of many Palestinian civilians, succeeded in receiving the world attention, in the form of protests from various dimensions of the world, call